Analysis The Use of Shopee Paylater on Student Purchasing Power From the Maslahah Perspective - Siti Anisa Simamora; Tuti Anggraini; Purnama Ramadani Silalahi (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
Paylater services offer significant convenience. By using paylater, students can make purchases without having to pay immediately in cash, but by paying later within a certain time period determined by the service provider. This research aims to determine the use of paylater on the purchasing power of students' reviews from maslahah. This research uses a qualitative approach, with qualitative phenomenology as the type of approach chosen. This research data was obtained through document study and observation and interviews as the main data. The subjects in this research were students from the Faculty of Islamic Economics & Business who used paylater, including Shopee Paylater. consisting of 30 students.  In this research, the data analysis method consists of three stages: data reduction, data presentation, and data verification. The research results show that although Shopee PayLater provides benefits in the form of convenience and cost savings, especially in terms of shipping costs, the use of this service is still considered strange from a sharia perspective. The conclusion in this research is that the use of Paylater has been proven to increase students' purchasing power from a social perspective.Keywords: Paylater, Purchasing Power, Maslahah